Evaluating Sakti User Satisfaction: An Integration of the Delone & Mclean Model and the Technology Acceptance Model (A Study on Partner Work Units of the Type A1 State Treasury Office of Gorontalo) - Jerry Kurniawan Piri; Tri Handayani Amaliah; Hendra Pratama Danial (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the effect of system quality and information quality on user satisfaction of the Agency-Level Financial Application System (SAKTI), with perceived ease of use and perceived usefulness placed as intervening variables. SAKTI is a mandatory web-based system used by all government work units to manage state finances. The study integrates the DeLone and McLean Information System Success Model with the Technology Acceptance Model. It applies a quantitative explanatory design. Primary data were collected through a closed-ended questionnaire with a five-point Likert scale from 85 active SAKTI users at partner work units of the Type A1 State Treasury Office of Gorontalo. The sample was drawn through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4 (Ringle et al., 2024). The study tested eighteen hypotheses covering direct effects, single mediation, and sequential mediation. Eleven hypotheses were accepted and seven were rejected. System quality and information quality did not affect user satisfaction directly. Their effect ran through perceived ease of use and perceived usefulness. Perceived usefulness was the strongest direct predictor of user satisfaction. Information quality reached user satisfaction through a full sequential path, while system quality did not. The findings confirm that user beliefs carry the effect of objective system attributes on satisfaction.